The role of anxiety in mediating the relationship between information consumption and COVID-19 protective behaviours: Psychology, Health & Medicine. Issue 9 (21st October 2022) - van Antwerpen, Natasha; Turnbull, Deborah; Searston, Rachel A.
ABSTRACT: Throughout the COVID-19 pandemic, concerns have been raised about an 'infodemic', with information and misinformation being spread across multiple channels and mediums. Information consumption has also been associated with increased anxiety throughout the pandemic. Thus, the present study investigates the mediating role of state anxiety on the relationship between information consumption (defined as mean frequency of information consumption multiplied by number of information sources) and COVID-19 protective behaviours. We compare results across Australian and United States samples and account for personal risk perception and belief in misinformation about COVID-19. Cross-sectional data collected between 28 and 30 April 2020 were analysed using Bayesian structural equation modelling among participants from Australia (N = 201), and the United States (N = 306). State anxiety scores were above the conventional clinical cut-off. Information consumption was positively associated with state anxiety, personal risk perception, and COVID-19 protective behaviours in the Australian and the United States samples. Additionally, the relationship between information consumption and COVID-19 protective behaviours was positively mediated by state anxiety in both nations, suggesting some functional benefits of anxiety. Differences in risk perception and belief in misinformation existed between the Australian and United States sample. Findings provide support for current guidance from organisations such as the WHO, APA, and APS on limiting information consumption to reduce anxiety. To effectively communicate critical public health messaging while minimising potential burdens on mental health, there is a need to develop and test interventions that assist people in calibrating the extent and nature of their information consumption.